Developing and Validating an English Version of the meCUE Questionnaire for Measuring User Experience. (September 2016) - Minge, Michael; Thüring, Manfred; Wagner, Ingmar
Based on theC omponent model ofU serE xperience (CUE), a standardized questionnaire (meCUE) was developed measuring key aspects of user experience (UX) for interactive products. The questionnaire consists of 34 items and covers four components: product perceptions (usefulness, usability, visual aesthetics, status, commitment), user emotions (positive, negative), consequences of usage (intention to use, product loyalty), and overall judgment. The modules were separately validated in a series of studies. Therefore, meCUE can be easily adapted to specific research goals by simply choosing those modules which are required. The original German questionnaire was translated into an English version that was validated in an online study. Fifty-eight native English speakers assessed a wide variety of interactive products, such as cell phones, digital cameras, PCs, laptops, tablets, software and mobile applications. Results show that the English version reliably assesses the key components of UX and that the internal consistency of its scales is high.